PARTICIPATORY NATURE OF RECOVERY AND DEVELOPMENT PROCESSES OF UKRAINIAN COMMUNITIES - Семененко, Інна М.; Сєрєбряк, Ксенія І.; Бурко, Ярослав В. (Journal of Strategic Economic Research, 2024)
The recovery and development processes of Ukrainian communities should take place with provision of participatory nature of such processes. The involvement of citizens in recovery planning and decision-making in war-affected communities is important because recovery itself is designed to meet the needs of residents and return them to their communities. Unfortunately, the relevant legislative regulations do not adequately take into account the involvement of citizens in the recovery and development processes. The purpose of the article is to identify the main areas of recovery and development of war-affected communities and to determine the readiness of community residents to participate in recovery processes using the example of the VNG International technical assistance project, which deals with local recovery. The project used various forms of community participation in addressing local issues. In particular, when developing plans for recovery and development of war-affected communities, a survey of residents of these communities was conducted to assess security issues and identify key areas for their recovery and further development. The survey revealed the percentage of people who have already returned or plan to return to their communities, as well as those who do not plan to return. The key reasons that influence this choice were also identified. The identified reasons correlate with the main areas of recovery, which were identified by community residents as key and those, which require priority attention. The results of the survey revealed the readiness of community residents to participate in the processes of recovery and reconstruction of communities, as well as the directions and ways in which residents are ready to join these processes. Focusing attention on solving the identified problems and achieving the tasks that are important to the residents will facilitate their return home.